Social diffusion of religious values within families: Conceptual and methodological considerations - Oliver Arránz Becker; Daniel Lois; Anja Steinbach (Universität Duisburg-Essen, Institut für Soziologie, 2016)
Family members create for each other the social context in which family behavior and personality development take place. The importance of social influence in families is evidenced empirically by family members' great similarity on a wide variety of characteristics. Focusing on intrafamily convergence on religiosity, the study discuses empirical methods of dyadic analysis and illustrates their use with an analysis of horizontal intracouple alignment and vertical intergenerational transmission. In addition to the finding that experiences during religious socialization in the parental home have a stronger impact than partner influences in adulthood, the analyses show that social context effects are stronger when the interaction dyad is more cohesive, as measured by, for example, relationship quality. – – Familienmitglieder repräsentieren füreinander jeweils gegenseitig den sozialen Kontext, innerhalb dessen sich familiales Handeln und individuelle Persönlichkeitsentwicklung abspielen. Soziale Einflüsse in Familien äußern sich empirisch in einer überzufälligen Ähnlichkeit der Familienmitglieder hinsichtlich einer großen Bandbreite von Merkmalen. Der vorliegende Beitrag fokussiert auf die intrafamiliale Homogenisierung hinsichtlich Religiosität, wobei in einem empirischen Datenbeispiel horizontale Paar-Angleichungsprozesse sowie vertikale intergenerationale Transmissionsprozesse untersucht werden. Neben dem Befund, dass Sozialisationserfahrungen im Elternhaus bedeutsamer sind als spätere Partnereinflüsse, zeigen die Analysen, dass soziale Kontexteffekte umso stärker ausfallen, je größer die Kohäsion in der jeweiligen Interaktionsdyade ist; hier operationalisiert über die Beziehungsqualität.
urn:nbn:de:hbz:464-20160511-152037-9
Keywords: 300; Intergenerational Transmission; Homogamy; Religion; Dyadic Analysis; Socialization; Social Context; Intergenerationale Transmission; Homogamie; Religion; Dyadische Datenanalyse; Sozialisation; sozialer Kontext